Nonsmooth integral guiding potentials and asymptotic behaviour of solutions for inclusions with causal multioperators. (1st February 2020) - Kornev, S.; Obukhovskii, V.; Yao, J.-C.
Abstract : In the present paper, differential inclusions with a causal multioperator are considered. We apply the method of nonsmooth integral guiding potentials to the study of the problem on the asymptotic behaviour of solutions for such inclusions. We investigate both the case of a closed and convex-valued right-hand part and the case of a nonconvex-valued and lower semicontinuous right-hand part.